RETRACTED ARTICLE: Strontium doped bioglass incorporated hydrogel-based scaffold for amplified bone tissue regeneration - Hamed Manoochehri; Masoud Ghorbani; Mehrdad Moosazadeh Moghaddam; Mohammad Reza Nourani; Pooyan Makvandi; Esmaeel Sharifi (Scientific Reports)
Abstract Repairing of large bone injuries is an important problem in bone regeneration field. Thus, developing new therapeutic approaches such as tissue engineering using 3D scaffolds is necessary. Incorporation of some bioactive materials and trace elements can improve scaffold properties. We made chitosan/alginate/strontium-doped bioglass composite scaffolds with optimized properties for bone tissue engineering. Bioglass (BG) and Sr-doped bioglasses (Sr-BG) were synthesized using Sol–Gel method. Alginate-Chitosan (Alg/Cs) scaffold and scaffolds containing different ratio (10%, 20% and 30%) of BG (Alg/Cs/BG10, 20, 30) or Sr-BG (Alg/Cs/Sr-BG10, 20, 30) were fabricated using freeze drying method. Characterization of bioglasses/scaffolds was done using zeta sizer, FTIR, XRD, (FE) SEM and EDS. Also, mechanical strength, antibacterial effect degradation and swelling profile of scaffolds were evaluated. Bone differentiation efficiency and viability of MSCs on scaffolds were determined by Alizarin Red, ALP and MTT methods. Cell toxicity and antibacterial effect of bioglasses were determined using MTT, MIC and MBC methods. Incorporation of BG into Alg/Cs scaffolds amplified biomineralization and mechanical properties along with improved swelling ratio, degradation profile and cell differentiation. Mechanical strength and cell differentiation efficiency of Alg/Cs/BG20 scaffold was considerably higher than scaffolds with lower or higher BG concentrations. Alg/Cs/Sr-BG scaffolds had higher mechanical stability and more differentiation efficiency in comparison with Alg/Cs and Alg/Cs/BG scaffolds. Also, Mechanical strength and cell differentiation efficiency of Alg/Cs/Sr-BG20 scaffold was considerably higher than scaffolds with various Sr-BG concentrations. Biomineralization of Alg/Cs/BG scaffolds slightly was higher than Alg/Cs/Sr-BG scaffolds. Overall, we concluded that Alg/Cs/Sr-BG20 scaffolds are more suitable for repairing bone major injuries.